Social perception of the connectivity and quality of sidewalks in the Metropolitan Area of Panama - Jorge Quijada-Alarcón; Roberto Rodríguez-Rodríguez; Analissa Icaza; Nicoletta González-Cancelas; Gabriel Bethancourt-Lasso (Journal of Maps)
Sidewalks have become important for modern cities in order to ensure that their inhabitants can move to their different activities in an optimal and safe manner. This research examines the perception of residents of the metropolitan area of Panama on the connectivity and quality of sidewalks. The study of sidewalks has been generally focused on evaluating accessibility for people with reduced mobility and the elderly; and also, on improving pedestrian safety. Using georeferenced household surveys, we collected data with which we performed spatial analyses to illustrate the distribution of sidewalk conditions in the urban metropolitan area of Panama. In addition, through the use of various approaches, such as accessibility assessments, user surveys and road safety parameters, other analyses of importance to the research were developed. The main conclusion was that only 26.25% of the metropolitan urban area of Panama has sidewalks that allow adequate pedestrian traffic.